DOSAGE FORMS OF NONSTEROIDAL ANTI-INFLAMMATORY PHARMACEUTICAL SUBSTANCE FOR CONTROLLED RELEASE - S. A. Kedik; V. V. Suslov; I. P. Sedishev; T. T. Nguen; E. A. Shnyak (Разработка и регистрация лекарственных средств, 2019)
This review is about nonsteroidal anti-inflammatory drugs and different approaches to development of pharmaceutical forms for controlled nonsteroidal anti-inflammatory drug release. Natural and synthetic biocompatible polymers used as drug carriers were considered. Different methods used for production of polymeric microparticles and formulations of nonsteroidal anti-inflammatory agents based on them were discussed. Characterization of microparticles with encapsulated nonsteroidal anti-inflammatory agents was given.